Penerapan Motion Graphic Pada Animasi 2D Sirah Nabawiyah - Andra Hariadi Fernando; Sheanny Ocmi Sakti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to explore the application of 2D motion graphic animation in the educational animation series